Factors Related about Family Delay Bring Stroke Patient to Emergency Departments of Labuha Hospital - Sarni J. Ishak; Yuyun Yueniwati; Ns. Rinik Eko Kapti (GoAcademica Research & Publishing, 2020)
The late arrival of stroke patients to the hospital is still a problem that still occurs in hospitals in several regions in Indonesia. Delay in treatment of stroke patients causes permanent disability and death. The time it takes for stroke patients is less than 3 hours to get thrombolytic therapy, which is started when an attack occurs. Where, the effectiveness of therapy is determined by the time the patient arrives at the hospital. Patient arrival to the hospital affects patient outcomes. Purpose: to analyze the factors associated with family delays in bringing stroke patients to the ER at Labuha Hospital. This study used an observational analytic study design with a cross sectional design approach. The research location is in the Emergency Room of the Labuha Hospital. Research time was September-November, 2020. The sampling technique used nonprobability sampling with purposive sampling technique totaling 42 stroke patients. The measuring instrument used is a questionnaire. Based on the Spearman test, it shows the relationship between the factors of knowledge (p = 0.01), awareness (p = 0.03), decision making (p = 0.00), economy (p = 0.00) and behavior (p = 0.00) with family delays in bringing stroke patients to the ER at Labuha Hospital. The multiple linear regression test shows that awareness is the most dominant factor associated with family delay with the coefficient value β -11.051 compared to other factors. The time delay of stroke patients decreased when knowledge, awareness, decision making, economy and family behavior were good.